CHTOP in Chemoresistant Epithelial Ovarian Cancer: A Novel and Potential Therapeutic Target - Feng, Xiaojie; Bai, Xupeng; Ni, Jie; Wasinger, Valerie C.; Beretov, Julia; Zhu, Ying; Graham, Peter; Li, Yong (Frontiers in Oncology, 2019)
Objective. Chemoresistance is a major challenge in epithelial ovarian cancer (EOC) treatment. Chromatin target of protein arginine methyltransferase (CHTOP) was identified as a potential biomarker in chemoresistant EOC cell lines using label-free LC-MS/MS quantitative proteomics. Thus, the aim of this study is to investigate the role of CHTOP in chemoresistant EOC and the underlying mechanism. Methods. The expression of CHTOP in human ovarian cancer cells and tissues was detected using immunofluorescence (IF), western blot (WB), and immunohistochemistry (IHC), respectively. Flow cytometry and TUNEL assay were employed to detect the effect of CHTOP knockdown (KD) in chemoresistant EOC cell apoptosis, while colony and mammary sphere formation assays were used to evaluate its effect on cell stemness. The association of CHTOP with cell metastasis was determined using Matrigel invasion and wound-healing assays. Results. The higher level expression of CHTOP protein was found in chemoresistant EOC cells as compared to their sensitive parental cells or normal epithelial ovarian cells. Results from IHC and bioinformatic analysis showed CHTOP was highly expressed in human ovarian cancer tissues and associated with a poor progression-free survival in patients. In addition, CHTOP KD significantly enhanced cisplatin-induced apoptosis, reduced the stemness of chemoresistant EOC cells, and decreased their metastatic potential. Conclusion. Our findings suggest that CHTOP is associated with apoptosis, stemness, and metastasis in chemoresistant EOC cells and might be a promising target to overcome chemoresistance in EOC treatment.